A plantation-dominated forest transition in Chile. (October 2016) - Heilmayr, Robert; Echeverría, Cristian; Fuentes, Rodrigo; Lambin, Eric F.
Abstract: As one of the few countries in Latin America to have reversed persistent losses in tree cover, Chile may hold important insights for forest transition theory. However, existing studies have not provided methodologically consistent analyses at sufficient temporal and spatial scales to properly assess the state of Chile's forest transition. In the current study, we generate high-resolution maps of Chilean land use change between 1986, 2001 and 2011. We couple remote sensing with a review of historic assessments of Chile's forest resources to document long-term trends in forest extent. This historical review identifies multiple discrete forest transitions throughout Chile's history. These fluctuations in forest clearing emphasize that the cultural, economic and political forces that precipitate forest transitions can all be reversed. The remote sensing analysis calls into question official statistics indicating an expansion of native forests between 1986 and 2011. We find that increases in forest cover were largely driven by the expansion of forest plantations, rather than through native forest regeneration. Plantation forests directly displaced native forests in many locations, especially during the 1986–2001 period. Nevertheless, declines in the rate of forest conversion during the 2001–2011 period suggest that plantations are beginning to ease pressure on native forests. Graphical abstract: Highlights: Increasing tree cover was due to plantation expansion, not native forest growth. Native deforestation declined from 0.5 percent (1986–2001) to 0.1 percent (2001–2011). Chile has undergone multiple forest transitions over the course of its history.